OPTIMASI KOMPOSISI TEPUNG BERAS DAN FRAKSI ETANOL DAUN SENDOK (Plantago major, L) DALAM FORMULASI TABIR SURYA DENGAN METODE SIMPLEX LATTICE DESIGN - Sugihartini, Nining (Universitas Ahmad Dahlan, 2011)
Octyl methoxycinnamate is an active ingredient in sunscreen that will bedegradated after exposure by sunlight. On the other hand, antioxidants have potentialcapability as photoprotector which in this study is used the ethanol fraction of leaf ofPlantago major, L to support activity of OMS. In addition, rice flour is added toobecause it has the ability to reflect sunlight. The aim of this study is to obtain theoptimum composition of them, based on the effectivity of OMS. This study used threeformulas based on the simplex lattice design method with a comparison of octylmethoxycinnamate and rice flour as follows: FI (100%: 0%), the formula II (50%:50%), formula III (0%: 100%). All formulas were exposured by sunlight for 5 hours (at09:00 to 14:00 GMT) and in interval one hour samples were taken to measure the valueof % erythema transmission (% Te) and pigmentation (% Tp). Data were analysed toget the optimum composition which has the highest of response. The results showed that100% rice flour was the optimum addition to support activity of OMS as sunscreen withdecreasing of % erythema transmission and pigmentation was 200%, 75%,respectively.